Night Witches at war : the Soviet women pilots of World War II - Berglund, Bruce R. (Graphic library. Amazing World War II stories., 2020)
"Describes the creation of an all-female squadron of Soviet pilots, known as the Night Witches, in World War II and some of the major battles they fought in during the war"--Provided by publisher.